Charge-transfer interaction mediated organogels from 18β-glycyrrhetinic acid appended pyrene - Hu, Jun; Wu, Jindan; Wang, Qian; Ju, Yong (Beilstein Journal of Organic Chemistry, 2013)
We describe herein the two-component charge-transfer (CT) interaction induced organogel formation with 18β-glycyrrhetinic acid appended pyrene (GA-pyrene, 3) as the donor, and 2,4,7-trinitrofluorenone (TNF, 4) as the acceptor. The use of TNF (4) as a versatile electron acceptor in the formation of CT gels is demonstrated through the formation of gels in a variety of solvents. Thermal stability, stoichiometry, scanning electron microscopy (SEM), optical micrographs, and circular dichroism (CD) are performed on these CT gels to investigate their thermal and assembly properties. UV–vis, fluorescence, mass spectrometric as well as variable-temperature 1H NMR experiments on these gels suggest that the CT interaction is one of the major driving forces for the formation of these organogels.
Keywords: charge transfer; glycyrrhetinic acid; organogel; self-assembly